The Role of MicroRNA-21 and MicroRNA-145 as Biomarkers inUlcerative Colitis - Sabry, Fatimah Ahmed; Mahmood , Suhad saad (Iraqi Journal of Science, 2026)
MicroRNAs (miRNAs) are vital bioactive factors that are important in almost every kind of cellular events. It plays a crucial role in regulating gene expression and is implicated in various diseases. This study aims to identify and characterize the differential expression of miRNAs in ulcerative colitis tissues compared to normal tissues and investigate their potential as biomarkers for early diagnosis. Real-time PCR was used to profile miRNA expression in 20 ulcerative colitis samples and 20 matched normal tissues. Bioinformatics tools were used to analyze expression patterns and identify significantly deregulated miRNAs. The analysis revealed miRNAs with significantly altered expression levels in ulcerative colitis tissues. MiR-21 were found to be upregulated, while miR-145 was downregulated. These changes were validated by quantitative PCR. Specific miRNAs, particularly miR-21 and miR-145, hold promise as potential biomarkers for the diagnosis and prognosis of ulcerative colitis. Further research is needed to explore its roles in cancer and therapeutic potential.